The prevalence of general obesity, overweight and abdominal obesity in Iranian university students: a meta-analysis - Hojjati, Mahsa; Dehghan, Zahra; Salari, Nader; Abdolmaleki, Amir; Mohsenzadeh, Mehdi; Abdullahi, Ahmad; Khaleghi, Ali Asghar; Shohaimi, Shamarina; Mohammadi, Masoud (Elsevier BV, 2023)
Background: The global prevalence of obesity in all age groups is increasing in developing or developed countries. This systematic review and meta-analysis study aimed to investigate the overall prevalence of general obesity (GO), overweight (OW), and abdominal obesity (AO) in Iranian university students (IUSs). Methods: Eligible articles were collected based on systematic searching using the main keywords of “Obesity”, “Overweight”, “Abdominal Obesity”, and “Students” in SID, PubMed, Google Scholar, and ScienceDirect databases. Following screenings and quality assessment of the papers, the final included articles with available data were entered into the Comprehensive Meta-Analysis software (CMA). The heterogeneity index (I 2 ) was assessed and the publication bias was considered through the Egger test. Results: Following the selection of 10 studies (total sample size = 6831 IUSs), the overall GO prevalence in IUSs was detected 5.1 (95 CI:1.6–15.4), the overall OW prevalence was 17.7 (95 CI:12.5–24.5), The overall AO prevalence in IUSs was detected 12.5 (CI95 = 9.1–16.9). the highest OW prevalence was detected 15 (95 CI:10.4–21.3) in male IUSs, and the highest AO prevalence was reported 11.4 (95 CI:6.2–20.2) in male IUSs. Conclusion: Although the GO prevalence was not found high in IUSs, the prevalence of OW and AO were detected at a high level, especially in male students. Thus, planning effective educational measures in universities seems necessary to prevent the associated obesity complications. Health policymakers and the officials of the Ministry of Health, Science, Research and Technology are recommended to establish special attention to the nutrition and physical activity of male students.